The effect of fuel weight distribution on the aeroelastic instability of swept wings - Abd Halim, Abdul Kareem; Syed Mohamed Ali, Jaffar; Sulaeman, Erwin (MechAero Foundation for Technical Research & Education Excellence (MAFTREE), 2020)
In this work, a study has been conducted to observe the influence of fuel weight distribution on the flutter characteristics of a high aspect ratio swept wing. In this paper, B777-200 wing model having a 34º sweptback angle is used as a baseline and two other models with the swept angles of 0º (straight wing) and 30º (forward swept) are considered in this study. Aeroelastic analysis is performed ranging from sea level up to 35,000 ft and the influence of in-flight fuel management in several flight altitudes is also investigated. There are four different fuel distribution model are investigated and it was found that some fuel distribution configuration are more critical which may lead to flutter. Moreover it was found that the flight altitude significantly affects the aeroelastic instability.